Rapid terahertz beam profiling and antenna characterization with phase-shifting holography - Michal Mrnka; Harry Penketh; David B. Phillips; Euan Hendry (Scientific Reports, 2024)
Abstract In this paper we investigate the application of phase-shifting digital holography for the real-time characterization of electromagnetic sources in the THz frequency range. We use an off-the-shelf terahertz detector array composed of $$64 × 64$$ 64 × 64 power-sensitive pixels, over an area of $$96\,\hbox {mm} × 96\,\hbox {mm}$$ 96 mm × 96 mm , to record intensity interferograms cast between the coherent radiation emitted from a reference source and an unknown antenna under test. This approach parallelizes the acquisition process with respect to conventional near-field point scanning methods, reducing the measurement time by orders of magnitude. In our system, the measurement time is limited only by the refresh rate of the detector array and the speed of a delay line stage that is used to phase-shift the reference wave. As a proof-of-principle demonstration, we map the 2D near-field distribution and estimate the far-field radiation pattern emitted by a plano-convex PTFE spherical lens antenna illuminated by a diagonal horn at 290 GHz frequency with $$\sim \,1\,\hbox {Hz}$$ ∼ 1 Hz refresh rate.